A research note: Quality of financial inputs and management earnings forecast accuracy in Japan. Issue 2 (August 2017) - Muramiya, Katsuhiko; Takada, Tomomi
Abstract: We examine the relation between the quality of financial inputs (indirectly measured by the existence or otherwise of restatements of the condensed financial statements), and management forecast accuracy in Japan. The Japanese market provides a unique environment to identify firms with poor-quality financial inputs because the stock exchanges require firms simultaneously to disclose (1) condensed financial statements for the current year and (2) management forecasts for the following year in their financial highlights ( Kessan Tanshin ) after the settlement of financial accounts and board approval before the final financial statements are issued. The simultaneous disclosure of management forecasts and earnings announcements implies that the firms that have restated their financial highlights are relying on poor-quality financial inputs to generate the statements and, most likely, the earnings forecast, as well. Our results suggest that restatement firms are likely to use poor-quality financial inputs and consequently report less accurate management forecasts.